Simulated net ecosystem productivity of subtropical forests and its response to climate change in Zhejiang Province, China - Mao, Fangjie; Du, Huaqiang; Zhou, Guomo; Zheng, Junlong; Li, Xuejian; Xu, Yanxin; Huang, Zihao; Yin, Shiyan (The Science of the total environment, 2022)
Net ecosystem productivity (NEP) is an important index that indicates the carbon sequestration capacity of forest ecosystems. However, the effect of climate change on the spatiotemporal variability in NEP is still unclear. Using the Integrated Terrestrial Ecosystem Carbon-budget (InTEC) model, this study takes the typical subtropical forests in the Zhejiang Province, China as an example, simulated the spatiotemporal patterns of forest NEP from 1979 to 2079 based on historically observed climate data (1979–2015) and data from three representative concentration pathway (RCP) scenarios (RCP2.6, RCP4.5, and RCP8.5) provided by the Coupled Model Intercomparison Project 5 (CMIP5). We analyzed the responses of NEP at different forest age classes to the variation in meteorological factors. The NEP of Zhejiang's forests decreased from 1979 to 1985 and then increased from 1985 to 2015, with an annual increase rate of 9.66 g C·m−2·yr−1 and a cumulative NEP of 364.99 Tg·C. Forest NEP decreased from 2016 to 2079; however, the cumulative NEP continued to increase. The simulated cumulative NEP under the RCP2.6, RCP4.5, and RCP8.5 scenarios was 750 Tg·C, 866 Tg·C, and 958 Tg·C, respectively, at the end of 2079. Partial correlation analysis between forest NEP at different age stages and meteorological factors showed that temperature is the key climatic factor that affects the carbon sequestration capacity of juvenile forests (1979–1999), while precipitation is the key climatic factor that affects middle-aged forests (2000–2015) and mature forests (2016–2079). Adopting appropriate management strategies for forests, such as selective cutting of different ages, is critical for the subtropical forests to adapt to climate change and maintain their high carbon sink capacity. [Display omitted] •Subtropical forest NEP under the RCP scenarios during 1979–2079 was modeled by InTEC model.•The average cumulative NEP of different scenarios was 858 Tg·C at the end of 2079.•Temperature is the key climatic factor affects the NEP of juvenile forests.•Precipitation is the key climatic factor affects middle-aged and mature forests.